Jordbrukets påverkan på Östersjön - Andersson, Helena (2008)
The Baltic Sea, due to its special conditions, is a unique and vulnerable marine environment. There are many pressures that have an impact on the sea and one of the major problems is the extensive flow of nutrients from land. The most visible effect of the supply of nutrients is the annual algal blooms.